ATP treatment retards the senescence of postharvest carambola fruit via modulating the metabolisms of energy and respiration - Yongqing Guan; Jiaxin Wen; Luna Wang; Yunman Chen; Xiaoting Lu; Yixiong Lin; Hetong Lin; Hui Wang (Postharvest Biology and Technology, 2026)

Nitrate photolysis as major summer daytime sources of ambient HONO in Southeastern Coastal China - Ziying Chen; Feng Zhang; Lingling Xu; Ziyi Lin; Xiuwen Yong; Yuping Chen; Gaojie Chen; Xiaoting Ji; Xiaolong Fan; Lingjian Wang; Mengren Li; Jinsheng Chen (Atmospheric Research, 2026)

Tunicamycin-induced endoplasmic reticulum stress triggers ZBP1-Mediated PANoptosis in macrophages and mouse spleen - Hongkun Jiang; Chen Qian; Xiaoting Lin; Ximei Huang; Zila Wang; Faquan Lin (Molecular Biology Reports, 2026)

Changes of physicochemical, morphological, and biological properties of fucoidan from Monascus purpureus-fermented Undaria pinnatifida: Mechanisms and implications - Yuling Yang; Hong Lin; Xiaoting Fu (Food Hydrocolloids, 2026)

Unraveling the structure–performance relationship of Co–Co/Co–N dual active sites in ZIF-8 derived nitrogen–doped carbon catalysts for efficient N2O decomposition - Ke Zheng; Ruirui Wang; Longqing Wang; Ruifang Wu; Xiangqian Lin; Xiaoting Du; Liangliang Zhang; Chengming Zhang; Yongzhao Wang (Journal of Hazardous Materials, 2026)

Leucobacter faecis sp. nov., a Novel Actinomycete Isolated from Bat Feces of Rousettus and Hipposideros spp. - Yuyuan Huang; Jing Yang; Qinglian Qin; Zedan Yang; Xiaoting Wei; Ziwei Lin; Wenbo Luo; Wudi Wei; Zongxiang Yuan; Li Ye; Junjun Jiang; Shan Lu; et al. (Current Microbiology, 2026)

A unified framework for gross primary productivity with shifting dominant limitation states between water and light use efficiency constraints - Shixiong Du; Baowei Yan; Changmei Liang; Dongxu Yang; Xuerui Zhou; Jianbo Chang; Xiaoting Lin (Agricultural and Forest Meteorology, 2026)

Mapping and marker development of the rye-derived Hessian fly resistance gene H25 in wheat - Xiaoting Xu; Xuming Liu; Ming-Shun Chen; Amy Bernardo; Paul St. Amand; Xiaomao Lin; Sanzhen Liu; Katherine W. Jordan; Guihua Bai (Theoretical and Applied Genetics, 2026)

Development and validation of a prognostic nomogram for predicting the progression risk of HCC after lenvatinib therapy - Chen Xie; Shaohong Luo; Shen Lin; Xiaoting Huang; Xiuhua Weng; Xiongwei Xu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

USP7 protects histone H1.2 from proteasome-mediated degradation to facilitate DNA repair and pancreatic neuroendocrine neoplasms progression - Mujie Ye; Lin Xu; Ping Yu; Jialing Pan; Xiaoting Shi; Bingyan Xue; Na He; Ping Hu; Min Liu; Xintong Lu; Yuemei Xu; Yanling Xu; et al. (Science China Life Sciences, 2026)

Sex-specific associations between exposure to metal mixtures and mitochondrial DNA copy number: A repeated-measures study - Junxiu He; Xiaoting Ge; Sencai Lin; Yu Bao; Hong Cheng; Sihan Hu; Xiuming Feng; Qinghua Fan; Ying Yang; Xiaobo Yang (Journal of Environmental Sciences, 2026)

Integrated non-targeted metabolomics, enzyme activities and morphological analysis to elucidate the mechanisms underlying the enhancement of activity and flavor of Monascus purpureus fermented Undaria pinnatifida - Yuling Yang; Hong Lin; Xiaoting Fu (Food Research International, 2026)

Stable network complexity between bacterial community and dissolved organic matter remains under three-year consecutive nitrogen addition - Xiaochun Yuan; Quanxin Zeng; Qiufang Zhang; Cheng-Chung Liu; Junjian Wang; Liang Zeng; Kaimiao Lin; Chaoliang Chen; Weifeng Guo; Jiacong Zhou; Juyan Cui; Xiaoli Gao; et al. (Applied Soil Ecology, 2026)

Determination of dry soil layer and vertical variations in soil thermal properties through interpretation of heat pulse signals using deep learning-based data assimilation - Xiaoting Xie; Lijie Li; Yili Lu; Lin Liu; Tusheng Ren (Journal of Hydrology, 2026)

The primary sources of ROx radicals in atmosphere: Oxidative capacity and self-purifying effect - Gaojie Chen; Ziyi Lin; Xiaoting Ji; Lingling Xu; Xiaolong Fan; Mengren Li; Youwei Hong; Jinsheng Chen (Journal of Environmental Sciences, 2026)

Structural design of wheat gluten using twin-screw extrusion: Focus on its application in starch-based gels - Xiaoshuai Yu; Zongrui Liu; Xiaoting Ma; Jiangkai Zeng; Jinjie Huo; Yumin Duan; Xiaoqi Ma; Lin Wang; Yixin Peng; Peng Wang; Zhigang Xiao (Journal of Cereal Science, 2026)

LncRNA AC098613.1 promotes acute myeloid leukemia cell differentiation through CDC5L/ADAP1/NRD1 axis - Qingling Jiang; Xiaoting Wang; Hang Yao; Jince Wang; Peiyu Tang; Mingpeng Liang; Zhaohai Pan; Bohan Li; Chunhua Lin; Qinxuan Wu; Qi Wang; Qiusheng Zheng; et al. (Apoptosis, 2026)

Exposure to triclosan and triclocarban is associated with estrogen metabolism in Chinese pregnant women - Min Huang; Yi Wang; Yuanping Wang; Baochang Sun; Guankai Lin; Ke Zhao; Jiaqi Liu; You Zhou; Xiaoting Wen; Xiaoyang Xu; Sumiao Hong; Yuanyuan Chen; et al. (Environmental Research, 2026)

Underwater sea cucumber detection based on domain-invariant features - Fangqun Niu; Zejin Liu; Xinyu Zheng; Junyi Wang; Dexuan Zhang; Yuanshan Lin; Xiaoting Zhu; Shuai Yang; Wei Wang; Guodong Li (Aquaculture International, 2025)

CPK12 decodes effector-triggered calcium signaling and phosphorylates PIP2;1 to facilitate apoplastic ROS transport into the cytoplasm in Arabidopsis - Zhiyi Jia; Weiwei Yu; Xijie Guo; Jianwei Li; Fan Qi; Yayun Zhu; Xinzhong Cai; Xiaoting Li; Ning Li; Hansong Dong; Fucheng Lin; Yan Liang (Molecular Plant, 2025)

Microbial succession dynamics drive mesh-structured microfibers transformation in estuarine wetlands: Metagenomic and metabolomic evidence of oxidative stress adaptation - Yiming Lei; Lujian Lin; Yue Ke; Xiaoting Zhang; Hanyi Li; Guanglong Zhang; Jingchun Liu; Haoliang Lu; Chongling Yan; Hualong Hong (Chemical Engineering Journal, 2025)

Fermentation of Pyropia spp. seaweed: a comprehensive review on processing conditions, biological activities and potential applications in the food industry - Yuling Yang; Hong Lin; Xiaoting Fu (Critical Reviews in Food Science and Nutrition, 2025)

Organ-specific lithium accumulation and its toxic effects on female reproduction - Qigang Fan; Yi Sun; Qingjun Shen; Yuxin Wang; Jisheng Nie; Yanbing Lin; Shuaishuai Xing; Yan Li; Benhong Xu; Jianjun Liu; Xiaoting Shen; Guangbo Qu; et al. (Journal of Hazardous Materials, 2025)

Associations of Metal Mixtures with Lipid Profiles: Exploring the Mediating Role of Testosterone in a Cross-Sectional Study - Sencai Lin; Ying Yang; Junxiu He; Sihan Hu; Yu Bao; Xiaoting Ge; Xiaobo Yang (Biological Trace Element Research, 2025)

Association of cold weather and influenza infection with stroke: a 22-year time-series analysis - Zihan Yang; Yuchen Wei; Xiaoting Jiang; Conglu Li; Guozhang Lin; Yawen Wang; Ka Chun Chong (International Journal of Biometeorology, 2025)
Despite the significant adverse health effects and economic burden of stroke inpatients, there has been a paucity of research specifically analyzing and quantifying the association between meteorological factors, air pollutants, influenza infection, and stroke admissions. This study assessed the impact of environmental factors and influenza activity on stroke admissions in Hong Kong from 1998 to 2019, utilizing population-based records. We employed the number of weekly stroke admissions as the primary outcome measure and matched the number with meteorological factors and air pollutant concentrations. Strain-specific influenza-like illness-positive (ILI+) rates were used as a proxy indicator of influenza activity. A quasi-Poisson generalized additive model in combination with a distributed-lag non-linear model (DLNM) was employed to elucidate the relationship of interest. Over the 22-year period, a total of 1,170,882 stroke-related admissions were recorded in Hong Kong. The cumulative adjusted relative risk (ARR) of stroke admission was significantly increased (cumulative ARR = 1.106, 95% CI, 1.069–1.143) at the 5th percentile of temperature (i.e., 15.08 °C) compared with the median reference level. Using zero as the reference value, the cumulative adjusted relative risks of stroke admission were 1.030 (95% CI, 1.018–1.042) at the 95th percentile of ILI + A/H1N1 rate, and 1.022 (95% CI, 1.007–1.038) at the 95th percentile of ILI + total rate. In conclusion, cold weather and influenza infection are risk factors to stroke admissions. Public health strategies for preventing stroke should be considered such as advocating influenza vaccination programmes during winter.

Fumonisins in maize and its products from Dalian region, China, and risk assessment by deterministic and probabilistic approaches - Xiaoyun Song; Yue Song; Junjie Gu; Mei Zhang; Lei Zhang; Xiaonan Zheng; Lin Guo; Xiaoting Liu (Food Additives & Contaminants Part B-Surveillance, 2025)

Association of Blood Metals and Metal Mixtures with the Myocardial Enzyme Profile: An Occupational Population-Based Study in China - Xiaoting Ge; Junxiu He; Yuan Zheng; Qiuyue Wang; Hong Cheng; Yu Bao; Sencai Lin; Xiaobo Yang (Biological Trace Element Research, 2025)

Cardiotoxicity of tris(2-chloroethyl) phosphate exposure: Insights into the role of oxygen sensor mediated energy metabolism remodeling - Ze Zhang; Chuer Zheng; Xinya Gu; Rifat Zubair Ahmed; Hao Yin; Jingxu Zhang; Yongfeng Lin; Jiao Luo; Yong Niu; Xiaoting Jin; Yuxin Zheng (Journal of Hazardous Materials, 2025)

Microbial diversity and antibacterial mechanism of slightly acidic electrolyzed water against Pseudomonas fluorescens in razor clam during storage - Xiaoting Xuan; Ziyi Zhang; Haitao Shang; Zheliang Sheng; Yan Cui; Xudong Lin; Shanqiao Chen; Lin Zhu (Food Research International, 2025)

Inhibition of platelet activation process upon tris (2-chloroethyl) phosphate exposure: Role of PFKP-mediated glycolysis and the pentose phosphate pathway - Ziyuan Li; Pu Chen; Yongfeng Lin; Jingxu Zhang; Jian Ding; Rifat Zubair Ahmed; Xiaoting Jin; Yuxin Zheng (Environmental Pollution, 2025)

Elucidating contributions of meteorology and emissions to O3 variations in coastal city of China during 2019–2022: Insights from VOCs sources - Keran Zhang; Qiaoling Chen; Youwei Hong; Xiaoting Ji; Gaojie Chen; Ziyi Lin; Feng Zhang; Yu Wu; Zhigang Yi; Fuwang Zhang; Mazhan Zhuang; Jinsheng Chen (Environmental Pollution, 2025)

Nitrogen-driven shifts in molecular composition of soil dissolved organic matter linked to rare bacterial sub-communities - Xiaochun Yuan; Quanxin Zeng; Xinyu Bai; Xiaoqing Zhang; Xiaoting Fu; Mengxiao Ren; Juyan Cui; Qiufang Zhang; Xiaoli Gao; Jiacong Zhou; Yong Zheng; Kaimiao Lin; et al. (Science of The Total Environment, 2025)

Cross-sectional and Longitudinal Associations Between Metal Mixtures and Serum C3, C4: Result from the Manganese‑exposed Workers Healthy Cohort - Sencai Lin; Junxiu He; Yinghua Zhou; Yu Bao; Xiuming Feng; Hong Cheng; Haiqing Cai; Sihan Hu; Lin Wang; Yuan Zheng; Mengdi Zhang; Qinghua Fan; et al. (Biological Trace Element Research, 2025)

PFOS impairs cardiac function and energy metabolism under high-fat diet: Insights into role of circulating macrophage emphasized by exposure distribution - Ze Zhang; Hao Yin; Chuer Zheng; Zhenhua Yu; Rifat Zubair Ahmed; Yong Niu; Chengying Zhou; Jian Ding; Huan Lin; Yongfeng Lin; Yuxin Zheng; Xiaoting Jin (Science of The Total Environment, 2024)

Arsenic(III) sequestration by terrestrial-derived soil protein: Roles of redox-active moieties and Fe(III) - Lujian Lin; Bo Yuan; Shengjie Wu; Manlin Su; Hanyi Li; Xiaoting Zhang; Guanglong Zhang; Hualong Hong; Haoliang Lu; Jingchun Liu; Chongling Yan (Journal of Hazardous Materials, 2024)

Effects of the Lactobacillus fermentation on Dendrobium officinale polysaccharide: Structural, physicochemical properties and in vitro bioactivities - Huasi Lin; Yanan Cheng; Lanxi Liang; Xiaoting Qin; Xuewen Dong; Yue Guo; Qiang Yu; Guowen Zhang; Xiaobo Hu (Food Bioscience, 2024)

Silk-based nanocomposite hydrogel balances immune homeostasis via targeting mitochondria for diabetic wound healing - Sijia Chen; Wanzhen Lei; Qi Liu; Xiaoting Wang; Kehan Chen; Xiaoyu Lin; Xuejiu Wang (Chemical Engineering Journal, 2024)

Inorganic Carbon Pools and Their Drivers in Grassland and Desert Soils - Longwei Dong; Jinzhi Ran; Jiali Luo; Lin Bai; Ying Sun; Muhammad Aqeel; Yahui Zhang; Xiaoting Wang; Qiajun Du; Junlan Xiong; Haiyang Gong; Qingqing Hou; et al. (Global Change Biology, 2024)
Inorganic carbon is an important component of soil carbon stocks, exerting a profound influence on climate change and ecosystem functioning. Drylands account for approximately 80% of the global soil inorganic carbon (SIC) pool within the top 200 cm. Despite its paramount importance, the components of SIC and their contributions to CO 2 fluxes have been largely overlooked, resulting in notable gaps in understanding its distribution, composition, and responses to environmental factors across ecosystems, especially in deserts and temperate grasslands. Utilizing a dataset of 6011 samples from 173 sites across 224 million hectares, the data revealed that deserts and grasslands in northwestern China contain 20 ± 2.5 and 5 ± 1.3 petagrams of SIC in the top 100 cm, representing 5.5 and 0.76 times the corresponding soil organic carbon stock, respectively. Pedogenic carbonates (PIC), formed by the dissolution and re‐precipitation of carbonates, dominated in grasslands, accounting for 60% of SIC with an area‐weighted density of 3.4 ± 0.4 kg C m −2 at 0–100 cm depth, while lithogenic carbonates (LIC), inherited from soil parent materials, prevailed in deserts, constituting 55% of SIC with an area‐weighted density of 7.1 ± 1.0 kg C m −2 . Soil parent materials and elevation determined the SIC stocks by regulating the formation and loss of LIC in deserts, whereas natural acidification, mainly induced by rhizosphere processes including cation uptake and H + release as well as precipitation, reduced SIC (mainly by PIC) in grasslands. Overall, the massive SIC pool underscores its irreplaceable role in maintaining the total carbon pool in drylands. This study sheds light on LIC and PIC and highlights the critical impact of natural acidification on SIC loss in grasslands.

Carrier effects of face mask-derived microplastics on metal ions: Enhanced adsorption by photoaging combined with biofilms, exemplified with Pb(Ⅱ) - Shuai Tang; Shengjia Ma; Lujian Lin; Yimei Ding; Xiaoting Zhang; Xiaowei Wu; Qun Zhang; Md. Nahid Pervez; Chengjin Cao; Yaping Zhao (Journal of Hazardous Materials, 2024)

Effect of environmental exposome and influenza infection on febrile seizure in children over 22 years: a time series analysis - Xiaoting Jiang; Conglu Li; Qianying Yue; Yuchen Wei; Yawen Wang; Xiang Qian Lao; Guozhang Lin; Ka Chun Chong (International Journal of Biometeorology, 2024)
Febrile seizures are convulsions predominately occurring in young children. The effects of various exposomes, including influenza infection and external environmental factors, on febrile seizures have not been well-studied. In this study, we elucidated the relationships between ambient temperature, air pollutants, influenza infection, and febrile seizures using 22-year territory-wide hospitalization data in Hong Kong. The aggregated data were matched with the meteorological records and air pollutant concentrations. All-type and type-specific influenza-like illness positive (ILI+) rates were used as proxies for influenza activity. Distributed lag non-linear model in conjunction with the quasi-poisson generalized additive model was used to examine the associations of interest. According to the results, all-type influenza infections were significantly associated with an increased risk of hospital admissions for febrile seizures (cumulative adjusted relative risk [ARR] = 1.59 at 95th percentile vs. 0; 95% CI, 1.51–1.68). The effect of ILI + A/H3N2 on febrile seizure was more pronounced than other type-specific ILI + rates. A low mean ambient temperature was identified as a significant risk factor for febrile seizures (cumulative ARR = 1.50 at 5th percentile vs. median; 95% CI, 1.35–1.66), while the redox-weighted oxidant capacity and sulfur dioxide were not associated with febrile seizures. In conclusion, our study underscores that influenza infections and exposure to cold conditions were related to an increased risk of febrile seizures in children. Thus, we advocate for influenza vaccination before the onset of the cold season for children to mitigate the burden of febrile seizures.

Dynamic changes and the effects of key procedures on the characteristic aroma compounds of Lu’an Guapian green tea during the manufacturing process - Jieyao Yu; Jingzhe Li; Zhi Lin; Yin Zhu; Zhihui Feng; Dejiang Ni; Shengchun Zeng; Xuehong Zeng; Yijun Wang; Jingming Ning; Liang Zhang; Xiaochun Wan; et al. (Food Research International, 2024)

Different microbial functional traits drive bulk and rhizosphere soil phosphorus mobilization in an alpine meadow after nitrogen input - Bing Han; Yicheng He; Ji Chen; Yufei Wang; Lina Shi; Zhenrong Lin; Lu Yu; Xiaoting Wei; Wantong Zhang; Yiyi Geng; Xinqing Shao; Shangang Jia (Science of The Total Environment, 2024)

Maize Soybean Relay Strip Intercropping Increases N Uptake by Coordinating Crop Configuration to Improve Root Physiological Activity - Xinyue Peng; Xueli Yang; Junbo Ren; Lida Yang; Ping Lin; Kai Luo; Xiaoting Yuan; Jiangli Luo; Yuze Li; Wenyu Yang; Taiwen Yong (Journal of Soil Science and Plant Nutrition, 2024)

Preparation of Fe single-atom carbon materials for DMFC and ZAB cathodic ORR catalysts based on the natural corn stalk binder/corn stalk biomass composite - Xiaoting Zhao; Xieraili Maimaitiyiming; Mamutjan Tursun; He Lin (Fuel, 2024)

Photochemical pollution during summertime in a coastal city of Southeast China: Ozone formation and influencing factors - Gaojie Chen; Xiaoting Ji; Jinsheng Chen; Lingling Xu; Baoye Hu; Ziyi Lin; Xiaolong Fan; Mengren Li; Youwei Hong; Jinfang Chen (Atmospheric Research, 2024)

Global multifaceted biodiversity patterns, centers, and conservation needs in angiosperms - Ao Luo; Yaoqi Li; Nawal Shrestha; Xiaoting Xu; Xiangyan Su; Yichao Li; Tong Lyu; Kilara Waris; Zhiyao Tang; Xiaojuan Liu; Luxiang Lin; Yongsheng Chen; et al. (Science China Life Sciences, 2024)

Rare DNAJC7 Variants May Play a Minor Role in Chinese Patients with ALS - Shichan Wang; Xiaoting Zheng; Qianqian Wei; Junyu Lin; Tianmi Yang; Yi Xiao; Qirui Jiang; Chunyu Li; Huifang Shang (Molecular Neurobiology, 2024)

Meteorological impacts on the unexpected ozone pollution in coastal cities of China during the unprecedented hot summer of 2022 - Xiaoting Ji; Gaojie Chen; Jinsheng Chen; Lingling Xu; Ziyi Lin; Keran Zhang; Xiaolong Fan; Mengren Li; Fuwang Zhang; Hong Wang; Zhi Huang; Youwei Hong (Science of The Total Environment, 2024)

Soil properties and fungal community jointly explain N2O emissions following N and P enrichment in an alpine meadow - Zhenrong Lin; Lina Shi; Xiaoting Wei; Bing Han; Cuoji Peng; Zeying Yao; Yicheng He; Qing Xiao; Xinmin Lu; Yanfang Deng; Huakun Zhou; Kesi Liu; et al. (Environmental Pollution, 2024)

Emission characteristics of carbonyl compounds from open burning of typical subtropical biomass in South China - Chunlin Zhang; Yiting Cai; Qian Yao; Xiaoting Liu; Lin Song; Jiangyong Li; Shuo Deng; Hao Wang; Boguang Wang (Chemosphere, 2024)

Crucial physicochemical factors mediating mitochondrial toxicity of nanoparticles at noncytotoxic concentration - Ze Zhang; Gan Miao; Lin Lu; Hao Yin; Yingzhu Wang; Baoqiang Wang; Ruonan Pan; Chuer Zheng; Xiaoting Jin (Science of The Total Environment, 2024)

Iron plaque formation and its influences on the properties of polyethylene plastic surfaces in coastal wetlands: Abiotic factors and bacterial community - Xiaoting Zhang; Lujian Lin; Hanyi Li; Shanle Liu; Shuai Tang; Bo Yuan; Hualong Hong; Manlin Su; Jingchun Liu; Chongling Yan; Haoliang Lu (Journal of Hazardous Materials, 2024)

Association between multiple metals exposure and sleep disorders in a Chinese population: A mixture-based approach - Lu Yufu; Liu Qiumei; Zhang Tiantian; Cai Jiansheng; Tang Xu; Wei Yanfei; Mo Xiaoting; Huang Shenxiang; Lin Yinxia; Li You; Luo Tingyu; Qin Jian; et al. (Chemosphere, 2023)

“Cocktail” of environmental chemicals and early reproductive outcomes of IVF: The insight from paternal and maternal exposure - Pan Yang; Jinying Xie; Songyi Huang; Xiaojie Li; Langjing Deng; Jinglei Zhang; Lin Chen; Nanxin Wu; Guangtong Huang; Canquan Zhou; Li Xiao; Xiaoting Shen (Journal of Environmental Management, 2023)

Quality changes and path analysis of color degradation of Dendrobium officinale flower juice during storage - Xuewen Dong; Jie Tang; Xiaoting Qin; Shenglan Tian; Huasi Lin; Qiang Yu; Xiaobo Hu; Mingyong Xie (Food Bioscience, 2023)

Photochemistry in the urban agglomeration along the coastline of southeastern China: Pollution mechanism and control implication - Gaojie Chen; Qiao Shi; Lingling Xu; Shaocai Yu; Ziyi Lin; Xiaoting Ji; Xiaolong Fan; Youwei Hong; Mengren Li; Fuwang Zhang; Jinfang Chen; Jinsheng Chen (Science of The Total Environment, 2023)

Feedback dynamics between precipitation, temperature, and soil moisture in China and their possible driving mechanisms under a changing environment - Xue Lin; Shengzhi Huang; Jianfeng Li; Qiang Huang; Haiyun Shi; Dunxian She; Guoyong Leng; Xiaoting Wei; Wenwen Guo; Yongqiang Liu; Jing Luo (Atmospheric Research, 2023)

Preliminary investigation of building damage in Hatay under February 6, 2023 Turkey earthquakes - Tao Wang; Jie Chen; Yujiang Zhou; Xiaoqing Wang; Xuchuan Lin; Xiaoting Wang; Qingxue Shang (Earthquake Engineering and Engineering Vibration, 2023)

Associations of metal mixtures with thyroid function and potential interactions with iodine status: results from a cross-sectional study in MEWHC - Xiaoting Ge; Junxiu He; Sencai Lin; Yu Bao; Yuan Zheng; Hong Cheng; Haiqing Cai; Xiuming Feng; Wenjun Yang; Sihan Hu; Lin Wang; Qijing Liao; et al. (Environmental Science and Pollution Research, 2023)

Association of CYP19A1 Gene, Plasma Zinc, and Urinary Zinc with the Risk of Type 2 Diabetes Mellitus in a Chinese Population - Xuexiu Wang; Yujian Liang; Qiumei Liu; Jiansheng Cai; Xu Tang; Shuzhen Liu; Junling Zhang; Min Xu; Chunmei Wei; Xiaoting Mo; Yanfei Wei; Yinxia Lin; et al. (Biological Trace Element Research, 2023)

Association between barium exposed, CYP19A1 and central obesity: A cross-sectional study in rural China - Yufu Lu; Lidong Qin; Yanfei Wei; Xiaoting Mo; Xu Tang; Qiumei Liu; Shuzhen Liu; Junling Zhang; Min Xu; Chunmei Wei; Shenxiang Huang; Yinxia Lin; et al. (Journal of Trace Elements in Medicine and Biology, 2023)

Seasonal variation of aerosol optical properties in a coastal city of southeast China: Based on one year of measurements - Lingjun Li; Mengren Li; Siqing Zhang; Liqian Yin; Xiaoting Ji; Yuping Chen; Chao Dong; Lingling Xu; Xiaolong Fan; Gaojie Chen; Ziyi Lin; Youwei Hong; et al. (Atmospheric Environment, 2023)

Associations of Dietary and Plasma Copper Levels with Liver Function in a Chinese Population - Yanfei Wei; Jiansheng Cai; Xiaoting Mo; Min Xu; Qiumei Liu; Junling Zhang; Shuzhen Liu; Yinxia Lin; Shenxiang Huang; Jian Qin; Zhiyong Zhang (Biological Trace Element Research, 2023)

Root-derived C distribution drives N transport and transformation after 13C and 15 N labelling on paddy and upland soils - Xiaoting Wang; Ruirui Chen; Evangelos Petropoulos; Bingqian Yu; Xiangui Lin; Youzhi Feng (Biology and Fertility of Soils, 2023)

Sex-Specific Associations of Urinary Metals with Renal Function: a Cross-sectional Study in China - Yinxia Lin; Jiansheng Cai; Qiumei Liu; Xiaoting Mo; Min Xu; Junling Zhang; Shuzhen Liu; Chunmei Wei; Yanfei Wei; Shenxiang Huang; Tingyu Mai; Dechan Tan; et al. (Biological Trace Element Research, 2023)

Impact of Tropical Cyclones over the North Indian Ocean on Weather in China and Related Forecasting Techniques: A Review of Progress - Ying Li; Chuanhai Qian; Xiaoting Fan; Beiyao Liu; Wei Ye; Jialu Lin (Journal of Meteorological Research, 2023)

Association of Dietary and Plasma Magnesium with Glycaemic Markers in a Chinese Population - Min Xu; Jiansheng Cai; Xiaoting Mo; Qiumei Liu; Junling Zhang; Yanfei Wei; Shuzhen Liu; Yinxia Lin; Shenxiang Huang; Chunbao Mo; Tingyu Mai; Dechan Tan; et al. (Biological Trace Element Research, 2023)

Palladium nanoparticles supported on LDH: A highly efficient and recyclable heterogeneous catalyst for the Heck reaction - Hao Sun; Chenzhe Xu; Xiaoting Yang; Lei Tao; Zheng Wang; Haitao Zhang; Xiang Ji; Juanjuan Ma; Lin Liu; Zhiwei Tong; Zhong Chen (Applied Clay Science, 2023)

Pyroptosis in inflammation-related respiratory disease - Yuanyu Feng; Min Li; Xiaoting Yangzhong; Xifeng Zhang; Anju Zu; Yunjiao Hou; Lin Li; Shibo Sun (Journal of Physiology and Biochemistry, 2022)
Pyroptosis is commonly induced by the gasdermin (GSDM) family and is accompanied by the release of inflammatory cytokines such as IL-1β and IL-18. Recently, increasing evidence suggests that pyroptosis plays a role in respiratory diseases. This review aimed to summarize the roles and mechanisms of pyroptosis in inflammation-related respiratory diseases. There are several pathways involved in pyroptosis, such as the canonical inflammasome-induced pathway, non-canonical inflammasome-induced pathway, caspase-1/3/6/7/GSDMB pathway, caspase-8/GSDMC pathway, caspase-8/GSDMD pathway, and caspase-3/GSEME pathway. Pyroptosis may be involved in asthma, chronic obstructive pulmonary disease (COPD), lung cancer, acute lung injury (ALI), silicosis, pulmonary hypertension (PH), and tuberculosis (TB), in which the NLRP3 inflammasome-induced pathway is mostly highlighted. Pyroptosis contributes to the deterioration of asthma, COPD, ALI, silicosis, and PH. In addition, pyroptosis has dual effects on lung cancer and TB. Additionally, whether pyroptosis participates in cystic fibrosis (CF) and sarcoidosis or not is largely unknown, though the activation of NLRP3 inflammasome is found in CF and sarcoidosis. In conclusion, pyroptosis may play a role in inflammation-related respiratory diseases, providing new therapeutic targets.

The full-length genome sequence of a novel amalgavirus in Lilium spp. in China - Yanyan Huo; Xiaoting Li; Jiale Zhou; Shengjie Lin; Jiahao Ding; Huan Liu; Jianglian Yu; Ni Hong; Guoping Wang; Fang Ding (Archives of Virology, 2022)

A Novel Preparation Method for Effervescent Tablets of Xianganfang Containing Fresh Juice using a Semi-Solid Extrusion 3D Printer with Three Cartridge Holders - Xiangru Dong; Wenfang Zhang; Xiaoting Wang; Sijia Liu; Jiawei Liang; Chunqiao Liufu; Shaofeng Zeng; Jiali Pang; Siting Li; Lingjuan Xiong; Guoyan Zhou; Weixing Zhu; et al. (AAPS PharmSciTech, 2022)

Associations Between Plasma Metals and Cognitive Function in People Aged 60 and Above - Junling Zhang; Qiumei Liu; Min Xu; Jiansheng Cai; Yanfei Wei; Yinxia Lin; Xiaoting Mo; Shenxiang Huang; Shuzhen Liu; Chunbao Mo; Tingyu Mai; Dechan Tan; et al. (Biological Trace Element Research, 2022)

The effects of dark treatment on photosynthesis and growth in young and mature leaves of Syzygium rehderianum - ZhengChao Yu; Wei Lin; XiaoTing Zheng; YanNa Luo; ChangLian Peng (Brazilian Journal of Botany, 2021)

Whether the carbon emission from green roofs can be effectively mitigated by recycling waste building material as green roof substrate during five-year operation? - Liangqian Fan; Jingting Wang; Xiaoling Liu; Hongbing Luo; Ke Zhang; Xiaoying Fu; Mei Li; Xiaoting Li; Bing Jiang; Jia Chen; Shuzhi Fu; You Mo; et al. (Environmental Science and Pollution Research, 2020)

Cu(OH)2 nanorods undergo sulfidation in water: in situ formation of CuO nanorods as intermediates and enhanced toxicity to Escherichia coli - Heming Su; Xiaoting Qian; Zhouhang Gu; Zhenlan Xu; Haijin Lou; Xinyun Bian; Tao Zeng; Daohui Lin; Juliane Filser; Lingxiangyu Li (Environmental Chemistry Letters, 2020)

Association between long-term occupational manganese exposure and bone quality among retired workers - Defu Li; Xiaoting Ge; Zhenfang Liu; Lulu Huang; Yanting Zhou; Peng Liu; Lian Qin; Suzhen Lin; Chaoqun Liu; Qingzhi Hou; Longman Li; Hong Cheng; et al. (Environmental Science and Pollution Research, 2020)

Molecular Mechanism, Evolution, Expression, and Functional Analyses of MAF/FLC Clade Members in Pak-Choi (Brassica rapa ssp. chinensis) - Lin Li; Peng Wu; Xiaoting Wu; Xilin Hou; Hong Wang; Tongkun Liu (Plant Molecular Biology Reporter, 2019)

Complete genome sequence of an alternavirus from the phytopathogenic fungus Fusarium incarnatum - Xiaoting Zhang; Yuan Xie; Fang Zhang; Hangjun Sun; Yingying Zhai; Songbai Zhang; Hongxia Yuan; Lin Zhou; Fei Gao; Honglian Li (Archives of Virology, 2019)

The complete genomic sequence of a novel megabirnavirus from Fusarium pseudograminearum, the causal agent of wheat crown rot - Xiaoting Zhang; Fei Gao; Fang Zhang; Yuan Xie; Lin Zhou; Hongxia Yuan; Songbai Zhang; Honglian Li (Archives of Virology, 2018)

Overexpression of AtWRKY28 and AtWRKY75 in Arabidopsis enhances resistance to oxalic acid and Sclerotinia sclerotiorum - Xiaoting Chen; Jun Liu; Guifang Lin; Airong Wang; Zonghua Wang; Guodong Lu (Plant Cell Reports, 2013)

Optimization of culturing condition and medium composition for the production of alginate lyase by a marine Vibrio sp. YKW-34 - Xiaoting Fu; Hong Lin; Sang Moo Kim (Journal of Ocean University of China, 2008)

Preliminary validation of high performance liquid chromatography method for detection of methyl-testosterone residue in carp muscle - Jie Jiang; Hong Lin; Xiaoting Fu; Mingming Li (Journal of Ocean University of China, 2005)